Designing Sustainable Organizations: Possible Clues from our Oldest Organizations - Hanson, Ph.D., Bruce (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
This paper develops some observations for designing sustainable organizations developed from lessons learned from some of our oldest organizations. This has implications for both the form and content of organizational design. Organizations need to remain oriented, flexible and innovative. The use of story is a valuable tool in organizational design, as the challenge of turbulence and change confront the organizational agent. Organizational fit includes not only ecological fit with the environment but our effect on that environment. To accomplish this over the years, we need to remain properly oriented. Consciousness becomes important, knowing who we are and how we contribute to the environment. The patience of the long-term perspective is important. There is much we can learn from ancient ways, however our power and knowledge have created entirely new challenges of how to manage our environment.